Previous Experience with Behavioral Control over Stress Blocks the Behavioral and Dorsal Raphe Nucleus Activating Effects of Later Uncontrollable Stress: Role of the Ventral Medial Prefrontal Cortex - Amat, Jose; Paul, Evan; Zarza, Christina; Watkins, Linda R; Maier, Steven F (The Journal of neuroscience, 2006)
Previous experience with stressors over which the subject has behavioral control blocks the typical behavioral consequences of subsequent exposure to stressors over which the organism has no behavioral control. The present experiments explored the involvement of the ventral medial prefrontal cortex (mPFCv) in mediating this “immunizing” or resilience producing effect of an initial experience with control. Behavioral immunization was blocked by inactivation of the mPFCv with muscimol at the time of the initial experience with control, as well as at the time of the later exposure to uncontrollable stress. Inhibition of protein synthesis within the mPFCv by anisomycin also blocked immunization when administered at the time of the initial controllable stress but had no effect when administered at the time of the later uncontrollable stress. Additional experiments found that the initial experience with control blocks the intense activation of serotonergic cells in the dorsal raphe nucleus that would normally be produced by uncontrollable stress, providing a mechanism for behavioral immunization. Furthermore, mPFCv activity during the initial controllable stressor was required for this effect to occur. These results suggest that the mPFCv is needed both to process information about the controllability of stressors and to utilize such information to regulate responses to subsequent stressors. Moreover, the mPFCv may be a site of storage or plasticity concerning controllability information. These results are consistent with recent research in other domains that explore the functions of the mPFCv.